2019
DOI: 10.1088/1742-5468/ab54b7
|View full text |Cite
|
Sign up to set email alerts
|

Coherent trapping in small quantum networks

Abstract: We consider a three-node fully connected network (Delta network) showing that a coherent population trapping phenomenon occurs, generalizing results for the Lambda network known to support a dark state. Transport in such structures provides signatures of detrapping, which can be triggered by external controls. In the presence of an environment it turns out to be sensitive to its Markovianity. Adiabatic modulation of the system's parameters may yield coherent population transfer, analogous to the stimulated R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…This Hamiltonian realizes the so‐called loop driving configuration for three‐level systems [ 44,45 ] (also referred to as Δ configuration [ 46 ] ) with complex (Peierls) couplings between each pair of states.…”
Section: Mapping Of Spin Models Into Multilevel Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…This Hamiltonian realizes the so‐called loop driving configuration for three‐level systems [ 44,45 ] (also referred to as Δ configuration [ 46 ] ) with complex (Peierls) couplings between each pair of states.…”
Section: Mapping Of Spin Models Into Multilevel Systemsmentioning
confidence: 99%
“…This type of driving, called loop‐drive or Δ configuration, has been discussed theoretically in various contexts in atomic physics. [ 43–46 ] Two of the drives realize the stimulated Raman adiabatic passage (STIRAP), while the third provides the counterdiabatic correction Hamiltonian required in saDSAP. This configuration results in the creation of a synthetic gauge potential with a gauge‐invariant Aharonov–Bohm phase, which can be controlled externally, allowing us to simulate the related gauge‐invariance phenomenon in spin systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10], it was shown that saSTIRAP works well in the noisy environment consisting of dissipation and Ornstein-Uhlenbeck dephasing. It was found that the performance of shortcuts to adiabaticity decreases with the correlation time of the Ornstein-Uhlenbeck noise [14], see also [15]. In the context of shortcuts to adiabaticity using the Lewis-Riesenfeld method, various noises (white noise, Ornstein-Uhlembeck noise, flicker noise, constant error) in the spring constant of the trap have been studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…They are thus ideal for continuous experiments with atomic cycling currents involving the excited state, as the removal of the decay channel allows the cycle to run for a longer period. Unfortunately, attempting to close the lambda system and generating a cycling current with a third field that directly couples the two ground states results in the destruction of the dark state, except in the restricting case when both driving strengths of the lambda subsystem are equal [10]. In general, the breakdown of the dark state in such a system brings population to the excited atomic state.…”
Section: Introductionmentioning
confidence: 99%